2020
DOI: 10.1097/mrr.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Goal-oriented attentional self-regulation training in individuals with acquired brain injury in a subacute phase: a pilot feasibility study

Abstract: The primary aim of this prospective pilot study was to assess feasibility of implementing goal-oriented attentional self-regulation (GOALS) training in Slovenia with patients with multiple cognitive deficits after acquired brain injury in acute phase of recovery. Seven patients with acquired brain injury (i.e. stroke, traumatic brain injury, and subarachnoid hemorrhage) with a mean postinjury time of 4.3 months (SD = 1.25) and mean age of 34.5 years (SD = 18.6) were recruited for the study. The group program c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As well, a small, single-arm pilot study assessed feasibility in 7 individuals with ABI of the goal-oriented attentional self-regulation (GOALS) program following ABI. They found significant pre- to postimprovements on neuropsychological measures of executive control and self-report of goal attainment 24. Lastly and as described earlier, Cantor et al18 found significant treatment effects, predominantly for self-reported executive function deficits.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…As well, a small, single-arm pilot study assessed feasibility in 7 individuals with ABI of the goal-oriented attentional self-regulation (GOALS) program following ABI. They found significant pre- to postimprovements on neuropsychological measures of executive control and self-report of goal attainment 24. Lastly and as described earlier, Cantor et al18 found significant treatment effects, predominantly for self-reported executive function deficits.…”
Section: Resultsmentioning
confidence: 57%
“…They found significant pre-to postimprovements on neuropsychological measures of executive control and self-report of goal attainment. 24 Lastly and as described earlier, Cantor et al 18 found significant treatment effects, predominantly for self-reported executive function deficits.…”
Section: Exec #2: Metacognitive Strategy Instructions (Eg Goal Manage...mentioning
confidence: 52%
See 2 more Smart Citations
“…Jeffay et al 11 recommend conducting it at least 6 months post-TBI, likely due to the limited research examining EF interventions in the subacute phase. [13][14][15][16] Both recommend strategies that focus on functional outcomes personally relevant to patients.…”
Section: Introductionmentioning
confidence: 99%